Penyuluhan Kesehatan tentang Adaptasi Kebiasaan Baru dan Pentingnya Vaksinasi COVID-19 pada Masyarakat idiiDesa Rumengkor Dua Kabupaten Minahasa - Mareyke Yolanda Lusia Sepang; Vina Putri Patandung (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Right way to handle COVID-19 that can be done to fight the COVID-19 pandemic is to implement new normal adaptations so as not to get infected this disease. In addition to adapting new normals, it is also very important for COVID-19 vaccination to suppress then increasing number of cases. The aim of this health education is public can understand about the implementation and benefits of adapting new normals in the current new normal era and the importance of COVID-19 vaccination to prevent transmission of COVID-19 in the community. Problem solving uses lecture and simulation methods, as well as video, leaflets, and posters. The target of this activity is the community of Rumengkor Dua Village, Minahasa Regency. Result of this health education can increase the knowledge and skills of the community about adapting new normal up to 94.28%, as well as the willingness to vaccinate for COVID-19 increased to 94.29%. At the end of the activity, participants can adaptation of new normals, especially 5M, even participants were able to carry out the act of wearing masks and washing hands properly an correctly, and most of the participants were willing to be vaccinated. The application of adaptation to new normals in the community is an effort to prevent disease transmission, so it is necessary to carry out health education on an ongoing basis by health workers by involving all levels of society starting from village, health cadres, and the community.